Analisis Permasalahan Dalam Praktek Profesi Advokat Terhadap Akses Keadilan di Masyarakat - Lila Graciella Yuwono; Meiliani; Yuwono Prianto (Jurnal Kewarganegaraan, 2024)
Abstract At this time, many problems occur in all fields of work, including in the field of Law. One of the problems faced today is the number of advocate organizations that exist, which is much more when compared to other professions. For example, the Indonesian Teachers Association (PGRI) is the only organization that oversees the teaching profession in Indonesia, while the advocate profession has many organizations, including the Indonesian Advocates Association (IKADIN), the Indonesian Advocates Association (AAI), the Indonesian Legal Advisors Association (IPHI), the Indonesian Advocates and Lawyers Association (HAPI), the Indonesian Lawyers Union (SPI), the Indonesian Legal Consultants Association (AKHI), the Capital Market Legal Consultants Association (HKHPM) and the Indonesian Sharia Lawyers Association (APSI). This has led to unhealthy competition among these advocate organizations. The purpose of this journal is to find a solution so that the number of advocate organizations does not limit the development of the advocate profession as a whole. With government intervention, it is hoped that prospective advocates can receive standardized and quality education and training, thus creating competent and professional advocates. This will help reduce unfair competition between advocate organizations and encourage better development of the advocate profession in Indonesia. Keywords: Advocate development, Government, Association Abstrak Pada saat ini, permasalahan banyak terjadi di segala bidang pekerjaan, termasuk dalam bidang Hukum. Salah satu masalah yang dihadapi saat ini adalah banyaknya organisasi advokat yang ada, yang jumlahnya jauh lebih banyak jika dibandingkan dengan profesi lain. Seperti contoh, Persatuan Guru Republik Indonesia (PGRI) adalah satu-satunya organisasi yang menaungi profesi guru di Indonesia, sedangkan profesi advokat memiliki banyak organisasi, diantaranya Ikatan Advokat Indonesia (IKADIN), Asosiasi Advokat Indonesia (AAI), Ikatan Penasihat Hukum Indonesia (IPHI), Himpunan Advokat dan Pengacara Indonesia (HAPI), Serikat Pengacara Indonesia (SPI), Asosiasi Konsultan Hukum Indonesia (AKHI), Himpunan Konsultan Hukum Pasar Modal (HKHPM) dan Asosiasi Pengacara Syariah Indonesia (APSI). Hal ini menyebabkan persaingan yang tidak sehat di antara organisasi-organisasi advokat tersebut. Tujuan dari pembuatan jurnal ini adalah untuk mencari solusi agar banyaknya organisasi-organisasi advokat tersebut tidak membatasi perkembangan profesi advokat secara keseluruhan. Dengan campur tangan pemerintah, diharapkan calon advokat dapat menerima pendidikan dan pelatihan yang terstandarisasi dan berkualitas, sehingga menciptakan advokat-advokat yang kompeten dan profesional. Hal ini akan membantu mengurangi persaingan tidak sehat antar organisasi-organisasi advokat dan mendorong perkembangan profesi advokat yang lebih baik di Indonesia. Kata Kunci: Perkembangan profesi advokat, Pemerintah, Asosiasi